Analisis Strategi Pemasaran Udang Vaname Dalam Meningkatkan Penjualan di PT XYZ - Fanggidae, Yrna Queen; Sirait, Tongam (Jurnal sosial dan sains, 2025)
This study aims to analyze the marketing strategy of PT XYZ's vannamei shrimp in facing market competition and to formulate effective strategies to increase sales in the domestic market. The research employs a descriptive qualitative approach using interviews, observations, and internal company documents. External environment analysis is conducted using the PESTLE framework and Porter’s Five Forces to identify opportunities and threats, while internal analysis applies Segmenting, Targeting, and Positioning (STP) and the 7P marketing mix to identify strengths and weaknesses. The findings are integrated through SWOT analysis and the QSPM matrix to generate strategic recommendations. The results indicate that PT XYZ still faces weaknesses in market reach and STP implementation, while global competition and oversupply pose significant external threats. The recommended strategies include strengthening domestic distribution and marketing channels, utilizing IoT technology to improve farming efficiency, and diversifying processed shrimp products. This research contributes theoretically to the development of marketing strategies for fishery commodities and provides practical recommendations for PT XYZ to enhance competitiveness and increase sales in local markets.